The impact of Covid-19 on cervical cancer screening (International Seven Journal of Health Research, 2023)
The pandemic caused by the SARS-Cov-19 virus was declared in March 2020, creating several effects on the provision of health services and society. In Primary Health Care, there was an interruption in the provision of preventive programs, including cervical cancer screening. Studies conducted in 2019 and 2020 show a reduction of close to 67% in certain regions of Brazil. Objectives: To analyze the impact of the COVID-19 pandemic on the collection of cytopathological examinations at the Jackson Roberto Carl Family Health Strategy in Blumenau-SC in 2020 and 2021. Methodology: To verify the impact of the COVID-19 pandemic, an accounting and descriptive analysis of the cytopathological exams performed between 01/30/2018 and 12/07/2021 was carried out regarding the number of exams per year of collection, based on the physical records of the ESF. Results: In the period from 2018 to 2021, 587 cytopathological exams were collected. In 2019, in the pre-pandemic, we had the highest number of screenings performed, totaling 210. Comparing 2019 and 2020 (first year of the COVID-19 pandemic), a significant drop in collections was observed from 210 to 20, respectively, representing a drop of approximately 90%. In 2021 there were 168 collections of this test, which represents the return of this preventive action. Conclusion: The significant drop in the performance of cytopathological tests imposed by the restrictive health measures of social distancing in 2020 refers to the need for active search of women in the screening group in order to recover this loss of coverage.